Analisis Penerapan Model Pembelajaran Berbasis Project-Based Learning terhadap Pembelajaran IPA di kelas IV SDN 064966 - Fenny Rizky Amelia; Devita Sari Purba; Wardah Nabila Syahnin; Selviona Dara Perbina; Sabaria Napitupulu; Jesminton Gultom (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
Elementary education plays an important role in building the foundation of students' knowledge and skills, especially in developing critical, creative, collaborative, and communicative thinking skills which are 21st century competencies. Natural Science (IPA) learning in Elementary Schools often faces challenges such as low active student participation and lack of relevance of the material to real life. As a solution, the PjBL model is proposed to improve the effectiveness of science learning in the classroom. This study uses a descriptive qualitative approach through observation, interviews, and documentation to analyze the complete implementation of PjBL, from planning, implementation, to results. The results of the implementation show that PjBL is able to increase student engagement, conceptual understanding, and collaborative skills as well as critical thinking through relevant and meaningful project activities. In addition, PjBL also fosters an attitude of caring for the environment and improves students' communication skills through group presentations. Thus, PjBL learning is proven to be effective in improving student learning outcomes. The obstacles that arise, such as time management and limited tools, can be overcome through intensive guidance and innovation in the use of simple or recycled materials.